Religion, spirituality & chronic illness: A scoping review and implications for health care practitioners. Issue 1 (2nd January 2018) - Roger, Kerstin Stieber; Hatala, Andrew
ABSTRACT: While the influence of institutional religion has decreased over the last 40–50 years, research suggests that a substantial proportion of those not attending religious services continue to engage in religious and spiritual practices on their own and refer to religion as a very important aspect in their lives, and as linked to more positive health outcomes, particularly for those living with chronic conditions. This article provides a scoping review to not only highlight the research that views religion and spirituality as valuable tools for coping with chronic illness conditions, but also to highlight research that explores those who may experience some religious/spiritual doubts or a gradual loss of religiosity or spirituality with the diagnosis of chronic conditions. Regardless of a clinician's beliefs, the authors argue that some awareness training of the value of religion and spirituality for some patients, can be beneficial. In a society facing an increasing plurality of faiths, this is deemed to be an invaluable discussion. In the end, clinical implications will be discussed.